TDP‐43 binds and transports G‐quadruplex‐containing mRNAs into neurites for local translation. (24th February 2016) - Ishiguro, Akira; Kimura, Nobuyuki; Watanabe, Yuto; Watanabe, Sumiko; Ishihama, Akira
Abstract : Growth and differentiation of the neurites depends on long‐distance transport of a specific set of mRNAs to restricted area and their local translation. Here, we found that a TAR DNA‐binding protein of 43 kDa in size (TDP‐43) plays an essential role in intracellular transport of mRNA. For identification of target RNAs recognized by TDP‐43, we purified TDP‐43 in soluble dimer form and subjected to in vitro systematic evolution of ligands by exponential enrichment (SELEX) screening. All the TDP‐43‐bound RNAs were found to contain G‐quadruplex (G4). Using a double‐fluorescent probe system, G4‐containing RNAs were found to be transported, together with TDP‐43, into the distal neurites. Two lines of evidence indicated that loss of function of TDP‐43 results in the neurodegenerative disorder: (i) amyotrophic lateral sclerosis (ALS)‐linked mutant TDP‐43M337V lacks the activity of binding and transport of G4‐containing mRNAs; and (ii) RNA containing G4‐forming GGGGCC repeat expansion from the ALS‐linked C9orf72 gene absorbs TDP‐43, thereby reducing the intracellular pool of functional TDP‐43. Taken together, we propose that TDP‐43 within neurons plays an essential role of mRNA transport into distal neurites for local translation, and thus, dysfunctions of TDP‐43 cause neural diseases such as ALS and frontotemporal lobar degeneration. Abstract : In this study, we found that trans‐activation response (TAR) DNA‐binding 43‐kDa protein (TDP‐43), recognizes G‐quadruplex‐containing mRNAs and transports them up to neurites for local translation. The success was based on the first purification of TDP‐43 in soluble dimer forms, allowing in vitro SELEX screening of target RNA molecules. Furthermore, we found that the loss‐of‐function mutation or over‐expression of TDP‐43 result in defect of intracellular transport of mRNAs in neural cells, thereby leading to the neurodegenerative disorder such as amyotrophic lateral sclerosis and frontotemporal lobar degeneration.